2008
DOI: 10.1161/hypertensionaha.108.110270
|View full text |Cite
|
Sign up to set email alerts
|

Angioedema Incidence in US Veterans Initiating Angiotensin-Converting Enzyme Inhibitors

Abstract: Abstract-Angioedema is a rare but potentially serious complication of angiotensin-converting enzyme inhibitor (ACE) use. We conducted a study to estimate incidence of ACE-related angioedema and explore its determinants in a large racially diverse patient population. We used linked medical and pharmacy records to identify all patients in the US Veterans Affairs Health Care System from April 1999 through December 2000 who received first prescriptions for antihypertensive medications. We studied 195 192 ACE ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
223
4
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(257 citation statements)
references
References 35 publications
18
223
4
12
Order By: Relevance
“…Other case control-studies found a higher frequency of OA in women [3,5] and, in our study, female sex was an independent risk factor for OA, which is in accordance to a large cohort study of medication-related angioedema incidence [9]. The reason for this sex difference is not clear, but may include the influence of sex hormones on the regulation of inflammation and an increased T h 2 immune response in women [10], which is further supported by the female predominance of chronic urticaria, a condition with a pathophysiology closely linked to acquired angioedema [11].…”
Section: Discussionsupporting
confidence: 93%
“…Other case control-studies found a higher frequency of OA in women [3,5] and, in our study, female sex was an independent risk factor for OA, which is in accordance to a large cohort study of medication-related angioedema incidence [9]. The reason for this sex difference is not clear, but may include the influence of sex hormones on the regulation of inflammation and an increased T h 2 immune response in women [10], which is further supported by the female predominance of chronic urticaria, a condition with a pathophysiology closely linked to acquired angioedema [11].…”
Section: Discussionsupporting
confidence: 93%
“…Still, it is likely that even more events would have occurred had the study been extended to the same length as other experiences. 2,7 Analysis of the factors that predicted angioedema events in OCTAVE confirmed that black patients were almost 3 times as likely as others to experience an episode. Previous histories indicative of allergic reactions, including rashes during treatment with other types of drugs, or episodes of seasonal allergy, were also predictive of angioedema.…”
Section: Estimating the Incidence Of Angioedema With Ace Inhibitorsmentioning
confidence: 91%
“…2 By studying all patients started on ACE inhibitors during a particular time period in the Veterans Affairs medical system, these investigators were able to count angioedema outcomes in a cohort numbering almost 200 000. This type of observation has the virtue of being carried out entirely within a closed healthcare system, so that all individuals presenting with angioedema-either as outpatients or inpatients-would have retrievable documentation of their diagnosis.…”
Section: Estimating the Incidence Of Angioedema With Ace Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations